Trace isolation and photometric determination of cadmium ions in water using thermally reduced graphene-modified hybrid sol-gel composite - Golmohammadi, Golnaz; Joolaei Ahranjani, Parham; Sereshti, Hassan; Dehghan, Kamine; Sadatfaraji, Hamed; Karami, Sajad; Rashidi Nodeh, Hamid (Separation science and technology, 2025)
This study presents the development and application of a thermally reduced graphene (TRG)-modified SiO₂-APTES composite for the extraction and preconcentration of cadmium (Cd (II)) ions from aqueous samples, with quantification by UV-Vis spectrophotometry. To enhance the selectivity of Cd(II) detection, diphenylthiocarbazone (dithizone) was used as a chelating agent prior to the extraction process. Critical parameters, including the type and volume of the desorption solvent, pH, adsorbent dosage, and salt concentration, were systematically investigated and optimized. The optimized method achieved a preconcentration factor of 200 for a 30 mL sample volume. The method demonstrated excellent analytical performance, with a linear dynamic range of 1.0-100 ng·mL −1 , a determination coefficient (R 2 ) of 0.995, a limit of detection (LOD) of 0.5 ng·mL −1 , and a relative standard deviation (RSD) of 4.1% at a Cd (II) concentration of 10 ng·mL −1 (n = 3). Application to real water samples yielded relative recoveries (RR) of approximately 94%, confirming the method's reliability and robustness. This approach combines high sensitivity, cost-effectiveness, and operational simplicity, making it a promising tool for trace-level cadmium detection in environmental and water quality monitoring applications.